Indicators of Incidence of Criminality in Mushin, Lagos; Role of Community Policing - Ogunmefun Folorunsho Muyideen; Olawunmi Kunle; Aluko Tolulope Evelyn; Aborisade Richard Abayomi; Amosun Olayemi Damilola (RIRAI Publisher, 2022)
The persistence reports on crime in Mushin are derogatory in nature and generate concerns for noble and intellectual researcher across Nigeria. Thus, Mushin was listed as one of the notorious areas in Lagos with constant cases of criminal activities that negate growth and development of the State. Extant literatures and Instinctual drive theory by Sigmund Freud was adopted for the justification of the inquiry. Mixed methods and cross sectional research was adopted with structured and unstructured questionnaires for collection of quantitative and qualitative data respectively from the participants at Mushin, Lagos. Yemane Taro (1963) formula for sample size was adopted but due to fear of unknown demonstrated by the participants after screening, coding and editing 185 quantitative instruments was found useful with 10 participants that willingly gave their consent to give verbal information The result gathered shows that there is relationship between personal characteristics and criminality at r=0.594, F-value yields F=99.837. Psychological factors and criminality at r=0.694, F=170.211. Parent socio economic factors and criminality at r=0.798, F=320.928. Environmental factors and criminality at r=0.654, F=136.807 Community policing and criminality at r=0.826, r=0.951 while the R-Square is 0.904. On this ground, the following recommendations were made; Nigerian government all levels, Philanthropist, Multinational organizations and the entire community members must come together to tackled the menace, Nigeria security should learn not to divulge classified information on issue of insecurity among others.